A Plausible Simultaneous Synthesis of Amino Acids and Simple Peptides on the Primordial Earth1. (25th June 2014) - Parker, Eric T.; Zhou, Manshui; Burton, Aaron S.; Glavin, Daniel P.; Dworkin, Jason P.; Krishnamurthy, Ramanarayanan; Fernández, Facundo M.; Bada, Jeffrey L.
Abstract Following his seminal work in 1953, Stanley Miller conducted an experiment in 1958 to study the polymerization of amino acids under simulated early Earth conditions. In the experiment, Miller sparked a gas mixture of CH4, NH3, and H2O, while intermittently adding the plausible prebiotic condensing reagent cyanamide. For unknown reasons, an analysis of the samples was not reported. We analyzed the archived samples for amino acids, dipeptides, and diketopiperazines by liquid chromatography, ion mobility spectrometry, and mass spectrometry. A dozen amino acids, 10 glycine‐containing dipeptides, and 3 glycine‐containing diketopiperazines were detected. Miller's experiment was repeated and similar polymerization products were observed. Aqueous heating experiments indicate that Strecker synthesis intermediates play a key role in facilitating polymerization. These results highlight the potential importance of condensing reagents in generating diversity within the prebiotic chemical inventory.